Applied trade policy modeling in 16 countries : insights and impacts from World Bank CGE based projects - Tarr, David G. (World Scientific studies in international economics, 2014)
This book focuses on the World Bank projects, led by the author, based on computable general equilibrium models of international trade policy. The chapters show an unusual combination of policy relevance, advice and impact, with academic rigor and international trade theory insights. The author discusses some of the policy contexts for the requests from developing and transition countries to the World Bank, the key trade theory or policy insights, policy recommendations and conclusions, and the policy impacts.